Photoelectric conversion element and photoelectric conversion element module

A curable adhesive composition combining acrylic adhesive with tackifying resin addresses the adhesiveness issue in photoelectric conversion elements, resulting in improved bonding and reduced moisture permeability.

JP7600560B2Active Publication Date: 2024-12-17ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020137102
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-14
Publication Date
2024-12-17
Estimated Expiration
2040-08-14

AI Technical Summary

Technical Problem

Existing curable adhesive compositions used in photoelectric conversion elements and modules, such as those described in Patent Document 1, do not adequately address the issue of adhesiveness, particularly in high-temperature environments and with inorganic materials.

Method used

A curable adhesive composition is formulated using an acrylic adhesive combined with a tackifying resin, specifically hydrocarbon or rosin resin, with defined molecular weight and softening point ranges, to enhance adhesiveness.

Benefits of technology

The composition forms a cured product with excellent adhesive properties, improving the bonding between substrates and reducing moisture permeability, thereby enhancing the performance and reliability of photoelectric conversion elements and modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600560000003
    Figure 0007600560000003
  • Figure 0007600560000001
    Figure 0007600560000001
  • Figure 0007600560000002
    Figure 0007600560000002
Patent Text Reader

Abstract

To provide a photoelectric conversion element having a hardening material which can exert an excellent adhesive property, and provide a photoelectric conversion element module.SOLUTION: A photoelectric conversion element comprises a hardening material of a hardening adhesive agent composition containing an acrylic adhesive and a tackifier resin, in which the tackifier resin is at least one of a hydrocarbon resin and a rosin system resin, the tackifier resin has a number average molecular weight of 200 or more and 2,000 or less, a weight average molecular weight of 500 or more and 5,000 or less, a Z-average molecular weight of 1,000 or more and 15,000 or less, and a ratio of the Z-average molecular weight to the weight average molecular weight of 1.0 or more 2.5 or less, and the tackifier resin has a softening point of 70°C or higher 170°C or lower.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photoelectric conversion element and a photoelectric conversion element module. [Background technology]

[0002] In recent years, curable adhesive compositions that can be cured by heat or light to bond members together have been used in the manufacture of photoelectric conversion elements and photoelectric conversion element modules that are composed of a plurality of photoelectric conversion elements. For example, in organic solar cell modules, a cured product of the curable adhesive composition is used for applications such as encapsulation of an electrolyte layer composed of an electrolyte solution. Specifically, Patent Document 1 reports that a sealing layer that is excellent in sealing properties, resistance to an electrolyte, adhesive strength at high temperatures, and the like can be formed by using a specific photocurable composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-265412 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the technique described in Patent Document 1 leaves room for improvement in terms of further improving the adhesiveness of a cured product formed using the curable adhesive composition.

[0005] Therefore, an object of the present invention is to provide a photoelectric conversion element and a photoelectric conversion element module that include a cured product that can exhibit excellent adhesive properties. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to achieve the above object, and have discovered that a cured product exhibiting excellent adhesive properties can be formed by using a curable adhesive composition obtained by mixing an acrylic adhesive with a tackifier resin having prescribed properties and consisting of a hydrocarbon resin and / or a rosin resin, thereby completing the present invention.

[0007] [1] That is, the present invention aims to advantageously solve the above problems, and the photoelectric conversion element of the present invention is a photoelectric conversion element having a cured product of a curable adhesive composition containing an acrylic adhesive and a tackifier resin, the tackifier resin being at least one of a hydrocarbon resin and a rosin resin, the tackifier resin having a number average molecular weight of 200 to 2,000, a weight average molecular weight of 500 to 5,000, a Z average molecular weight of 1,000 to 15,000, a ratio of the Z average molecular weight to the weight average molecular weight of 1.0 to 2.5, and the tackifier resin having a softening point of 70 ° C. to 170 ° C. If a curable adhesive composition obtained by mixing an acrylic adhesive with a hydrocarbon resin and / or a rosin resin having the above-mentioned predetermined properties is cured, a cured product having excellent adhesive properties can be obtained, and a photoelectric conversion element that can exhibit excellent performance, and a photoelectric conversion element module comprising a plurality of such photoelectric conversion elements connected together can be produced. In the present invention, the "number average molecular weight", "weight average molecular weight", "Z average molecular weight" and "softening point" of the tackifier resin can be measured by the methods described in the examples.

[0008] [2] In the photoelectric conversion element of the present invention, the tackifier resin preferably has a number average molecular weight of 200 to 1,000, a weight average molecular weight of 500 to 2,000, and a Z average molecular weight of 1,000 to 4,000. When the number average molecular weight, weight average molecular weight, and Z average molecular weight of the tackifier resin are within the above-mentioned ranges, respectively, the adhesiveness of the cured product formed from the curable adhesive composition can be further improved.

[0009] [3] In the photoelectric conversion element of the present invention, the acid value is preferably 0.01 KOHmg / g or more and 300 KOHmg / g or less. If the acid value of the tackifier resin is within the above range, the adhesiveness (particularly the adhesiveness to inorganic materials) of the cured product formed from the curable adhesive composition can be further improved. In the present invention, the "acid value" of the tackifier resin can be measured by the method described in the Examples.

[0010] [4] In the photoelectric conversion element of the present invention, the content of the tackifier resin is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the acrylic adhesive. If the content of the tackifier resin is within the above range, the adhesiveness of the cured product formed from the curable adhesive composition can be further improved.

[0011] [5] In the photoelectric conversion element of the present invention, the curable adhesive composition may further contain conductive particles.

[0012] [6] The photoelectric conversion element of the present invention is the photoelectric conversion element according to any one of the above [1] to [4], and is composed of a photoelectric conversion cell including a first substrate having a photoelectrode, a second substrate having a counter electrode facing the photoelectrode, two partition walls facing each other and interposed between the first substrate and the second substrate, and an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls, and at least one of the two partition walls is preferably made of a cured product of the curable adhesive composition. In the photoelectric conversion element having such a configuration, the partition wall made of the cured product of the curable adhesive composition can exhibit excellent adhesion.

[0013] [7] The photoelectric conversion element of the present invention is the photoelectric conversion element according to [5] or [6] above, comprising a first substrate having a photoelectrode, a second substrate having a counter electrode facing the photoelectrode, two partition walls interposed between the first substrate and the second substrate and facing each other, and an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls, and further comprising at least one of a cell connection part capable of electrically connecting the photoelectrode to a counter electrode belonging to another photoelectric conversion cell and a cell connection part capable of electrically connecting the counter electrode to a photoelectrode belonging to another photoelectric conversion cell, and at least one of the cell connection parts of the photoelectric conversion cell preferably contains a cured product of the curable adhesive composition further containing conductive particles. In the photoelectric conversion element having such a configuration, the cell connection part made of the cured product can exhibit excellent adhesiveness.

[0014] [8] The present invention also aims to advantageously solve the above problems, and the photoelectric conversion element module of the present invention is characterized in that it has a structure in which the photoelectric conversion elements described in any of [1] to [7] above are connected in series and / or in parallel. In this way, the photoelectric conversion element module formed by connecting any of the above-mentioned photoelectric conversion elements in multiple ways, at least in direct and in parallel, is excellent in various performances such as photoelectric conversion characteristics. Effect of the Invention

[0015] According to the present invention, it is possible to provide a photoelectric conversion element and a photoelectric conversion element module including a cured product capable of exhibiting excellent adhesive properties. [Brief description of the drawings]

[0016] [Figure 1] 1 is a cross-sectional view showing a schematic structure of an example of a photoelectric conversion element and a photoelectric conversion element module according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described in detail. The photoelectric conversion element of the present invention comprises a cured product formed from a curable resin composition that can be cured by light, heat, or the like. Moreover, the photoelectric conversion element module of the present invention is, for example, an organic solar cell module such as a dye-sensitized solar cell module, an organic thin-film solar cell module, or a perovskite solar cell module.

[0018] (Curable adhesive composition) The curable adhesive composition used in producing the photoelectric conversion element of the present invention contains at least an acrylic adhesive and a tackifier resin, and can optionally contain other components such as conductive particles depending on the application. Furthermore, according to the above-mentioned curable adhesive composition, it is possible to form a cured product with excellent adhesive properties, presumably because the acrylic adhesive and the tackifier resin having the specified properties can be well mixed.

[0019] The curable adhesive composition is not particularly limited, and may be a photocurable adhesive composition or a thermosetting adhesive composition. Among them, the curable adhesive composition used in the production of the photoelectric conversion element of the present invention is preferably a photocurable adhesive composition. If the curable adhesive composition is photocurable, it is possible to prevent deterioration due to heating, particularly in the manufacturing process of the photoelectric conversion element and the photoelectric conversion element module, and improve the performance of the obtained photoelectric conversion element and the photoelectric conversion element module.

[0020] <Acrylic adhesive> The acrylic adhesive is not particularly limited as long as it is a composition that can provide a cured product consisting of a polymer containing at least one selected from the group consisting of a repeating unit (acrylate unit) derived from an acrylate monomer (acrylic acid ester), a repeating unit (methacrylate unit) derived from a methacrylate monomer (methacrylic acid ester), and a repeating unit (alicyclic monofunctional (meth)acrylate unit) derived from an alicyclic monofunctional (meth)acrylate monomer by proceeding with curing such as a polymerization reaction due to light or heat. In the acrylic adhesive and curable adhesive composition, the monomer components such as the acrylate monomer, the methacrylate monomer, and the alicyclic monofunctional (meth)acrylate monomer may be in a non-polymerized state (monomer state) or in a polymerized state (oligomer, polymer state).

[0021] In the present invention, "(meth)acrylate" means acrylate and / or methacrylate. In the present invention, the term "alicyclic monofunctional (meth)acrylate monomer" refers to a (meth)acrylate monomer having one acryloyl group or methacryloyl group, and an ester residue (R in -C(=O)-OR) is an alicyclic hydrocarbon group. In the present invention, monomers that fall under the category of "alicyclic monofunctional (meth)acrylate monomers" are not included in acrylate monomers and methacrylate monomers.

[0022] In one embodiment of the present invention, the acrylic adhesive is a mixture of monomer components such as acrylate monomers, methacrylate monomers, and alicyclic monofunctional (meth)acrylate monomers, and a polymerization initiator.

[0023] [Monomer components] In the acrylic adhesive, the monomer component is not particularly limited as long as it contains at least one of an acrylate monomer, a methacrylate monomer, and an alicyclic monofunctional (meth)acrylate monomer, and may contain other monomer components (other monomers) besides these.

[0024] --Acrylate monomer-- Examples of acrylate monomers include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, decyl acrylate, lauryl acrylate, 2-propylheptyl acrylate, stearyl acrylate, octadecyl acrylate, nonyl acrylate, dodecyl acrylate, and benzyl acrylate. These may be used alone or in combination of two or more.

[0025] -Methacrylate monomer- Examples of methacrylate monomers include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, octyl methacrylate, isooctyl methacrylate, 2-ethylhexyl methacrylate, decyl methacrylate, lauryl methacrylate, 2-propylheptyl methacrylate, stearyl methacrylate, octadecyl methacrylate, nonyl methacrylate, dodecyl methacrylate, and benzyl methacrylate. These may be used alone or in combination of two or more.

[0026] In one embodiment of the present invention, among the above-mentioned acrylic acid esters and methacrylic acid esters, acrylic acid esters are preferred, acrylic acid alkyl esters are more preferred, and isooctyl acrylate, 2-ethylhexyl acrylate, n-butyl acrylate, and isobutyl acrylate are further preferred.

[0027] - Alicyclic monofunctional (meth)acrylate monomer - The alicyclic hydrocarbon group of the alicyclic monofunctional (meth)acrylate monomer is preferably an alicyclic hydrocarbon group that does not have a polar group such as a carboxyl group, an epoxy group, a phosphoric acid ester group, or a halogen group. Moreover, the alicyclic monofunctional (meth)acrylate monomer preferably has a dicyclopentanyl structure, a dicyclopentenyl structure, an adamantyl structure, or an isobornyl structure, and more preferably has a dicyclopentanyl structure, an adamantyl structure, or an isobornyl structure. That is, the alicyclic hydrocarbon group contained in the monomer is preferably a dicyclopentanyl group, a dicyclopentenyl group, an adamantyl group, or an isobornyl group. When the alicyclic hydrocarbon group has any of these structures, the moisture permeability of the obtained cured product can be reduced, while the adhesiveness can be further improved.

[0028] In addition, the total carbon number of the alicyclic monofunctional (meth)acrylate monomer is preferably 13 or more, more preferably 13 or more and 16 or less, even more preferably 13 or more and 15 or less, and particularly preferably 13 or 14, from the viewpoint of further improving the adhesion while reducing the moisture permeability of the obtained cured product.

[0029] Specific examples of the alicyclic monofunctional (meth)acrylate monomer include cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, dicyclopentenyl acrylate, dicyclopentenyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantyl acrylate, 1-adamantyl methacrylate, 2-methyladamantyl acrylate, and 2-methyladamantyl methacrylate. These may be used alone or in combination of two or more. Among these, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, dicyclopentenyl acrylate, and dicyclopentenyl methacrylate are preferred, and dicyclopentanyl acrylate and dicyclopentanyl methacrylate are more preferred.

[0030] The amount of the above-mentioned acrylate monomer, methacrylate monomer, and / or alicyclic monofunctional (meth)acrylate monomer contained in the acrylic adhesive is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, even more preferably 80% by mass or more and 100% by mass or less, and particularly preferably 90% by mass or more and 100% by mass or less, based on 100% by mass of the entire monomer component.

[0031] -Other monomers- The other monomer is not particularly limited as long as it is copolymerizable with the above-mentioned acrylate monomer, methacrylate monomer, and / or alicyclic monofunctional (meth)acrylate monomer. Examples of the other monomer include acrylic acid, itaconic acid, methacrylic acid, acrylonitrile, methacrylonitrile, vinyl acetate, cyanoethyl acrylate, maleic anhydride, hydroxyalkyl acrylate, β-carboxyethyl acrylate, neodecanoic acid, neononanoic acid, neopentanoic acid, vinyl ester of 2-ethylhexanoic acid or propionic acid, vinylidene chloride, styrene, vinyl toluene, alkyl vinyl ether, ethoxyethoxyethyl acrylate, methoxypolyethylene glycol acrylate, N,N-dimethylacrylamide, N-vinyl caprolactam, N-vinyl pyrrolidone, N-isopropylacrylamide, N,N-dimethyl acrylate, N-vinyl ... butylaminoethyl methacrylate, 2-[[(butylamino)carbonyl]oxy]ethyl acrylate, N,N-dimethylaminopropyl methacrylamide, N,N-diethylaminopropyl methacrylamide, N,N-dimethylaminoethyl acrylate, N,N-diethylaminoethyl acrylate, N,N-dimethylaminopropyl acrylate, N,N-diethylaminopropyl acrylate, N,N-diethylaminoethyl methacrylate, N,N-dimethylaminoethyl acrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-diethylaminoethyl acrylamide, and N,N-diethylaminoethyl methacrylamide.

[0032] As the other monomer, a polyfunctional (meth)acrylate monomer can also be used. Examples of the polyfunctional (meth)acrylate monomer include tri(meth)acrylates such as trimethylpropane tri(meth)acrylate, propoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, and pentaerythritol triacrylate; di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, alkoxylated 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, cyclohexanedimethanol di(meth)acrylate, alkoxylated cyclohexanedimethanol diacrylate, ethoxylated bisphenol A di(meth)acrylate, neopentyl glycol diacrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and urethane di(meth)acrylate; Examples include: In the present invention, a monomer that corresponds to the "polyfunctional (meth)acrylate monomer" is not included in the acrylate monomer and the methacrylate monomer.

[0033] The above-mentioned other monomers may be used alone or in combination of two or more. The amount of the above-mentioned other monomers contained in the acrylic adhesive is preferably 0% by mass or more and 50% by mass or less, more preferably 0% by mass or more and 30% by mass or less, even more preferably 0% by mass or more and 20% by mass or less, and particularly preferably 0% by mass or more and 10% by mass or less, with the entire monomer component being 100% by mass.

[0034] [Polymerization initiator] The polymerization initiator is not particularly limited as long as it is capable of polymerizing the above-mentioned monomer components, and known photoinitiators and thermal reaction initiators can be used, with photoinitiators being preferred.

[0035] -Photoinitiator- Examples of photoinitiators include substituted acetophenones such as benzyl dimethyl ketal and 1-hydroxycyclohexyl phenyl ketone, substituted α-ketol such as 2-methyl 2-hydroxypropiophenone, benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, anisoin methyl ether, aromatic sulfonyl chlorides, photoactive oximes, and azo-type initiators. These may be used alone or in combination of two or more. The amount of photoinitiator contained in the acrylic adhesive is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and even more preferably 0.05 parts by mass or more, per 100 parts by mass of the above-mentioned monomer component, and is preferably 5 parts by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less.

[0036] -Thermal reaction initiator- Examples of the thermal reaction initiator include azo, peroxide, persulfate, and redox reaction initiators. These may be used alone or in combination of two or more. The amount of the thermal reaction initiator contained in the acrylic adhesive is preferably 0.01 parts by mass or more, and more preferably 0.025 parts by mass or more, per 100 parts by mass of the above-mentioned monomer component, and is preferably 5 parts by mass or less, and more preferably 2 parts by mass or less.

[0037] [Example of acrylic adhesive] The acrylic adhesive is not particularly limited, but for example, compositions described in JP-T-2016-501290, JP-A-2020-007449, Japanese Patent No. 6319549, or Japanese Patent No. 6361862 can also be used.

[0038] <Tackifier resin> Examples of the tackifier resin include hydrocarbon resins and rosin-based resins. The hydrocarbon resins and rosin-based resins may be used alone or in combination.

[0039] [Hydrocarbon resin] The hydrocarbon resin is not particularly limited as long as it is a resin made of a polymer having a hydrocarbon as the main skeleton. The hydrocarbon resin may be modified with an acid or hydrogenated. Examples of the hydrocarbon resin include C5 petroleum resin, C5 / C9 petroleum resin (C5 / C9 resin), C9 petroleum resin, dicyclopentadiene resin, terpene resin, terpene phenol resin, aromatic modified terpene resin, alkylphenol-acetylene resin, indene resin, C9 resin containing indene, α-methylstyrene-indene copolymer resin, coumarone-indene resin, farnesene resin, polylimonene resin, etc. In addition, examples of the hydrocarbon resin include hydrocarbon resins prepared using monomers disclosed in JP 2018-2861 A, WO 2018 / 180462, or Japanese Patent No. 6102436. The hydrocarbon resins may be used alone or in combination of two or more kinds.

[0040] [Rosin-based resin] The rosin-based resin may be natural rosin or a derivative thereof (modified rosin). Specific examples of the rosin-based resin include partially disproportionated rosin, disproportionated rosin, hydrogenated rosin, maleic acid modified rosin, polymerized rosin, gum rosin, wood rosin, tall oil rosin, distilled rosin, dimer rosin, and rosin ester. Examples of rosin esters include glycerol and / or pentaerythritol esters of natural rosin and / or modified rosin, such as glycerol ester of pale wood rosin, glycerol ester of hydrogenated rosin, glycerol ester of polymerized rosin, pentaerythritol ester of hydrogenated rosin, and phenol-modified pentaerythritol ester of natural rosin. The rosin-based resins may be used alone or in combination of two or more kinds.

[0041] Among the above-mentioned tackifier resins, C5 / C9 petroleum resins, acid-modified C5 / C9 petroleum resins, gum rosin, and rosin esters are more preferred from the viewpoint of further improving the adhesiveness of the resulting cured product.

[0042] [Properties of tackifier resin] Here, the tackifier resin must have a number average molecular weight (Mn) of 200 or more and 2,000 or less, preferably 1,500 or less, and more preferably 1,000 or less. If the number average molecular weight of the tackifier resin is within the above-mentioned range, the tackifier resin will be well mixed with the acrylic adhesive, and the adhesiveness of the resulting cured product will be improved.

[0043] In addition, the tackifier resin must have a weight average molecular weight (Mw) of 500 or more and 5,000 or less, preferably 3,500 or less, and more preferably 2,000 or less. If the weight average molecular weight of the tackifier resin is within the above-mentioned range, the tackifier resin will be well mixed with the acrylic adhesive, and the adhesiveness of the resulting cured product will be improved.

[0044] Furthermore, the tackifier resin must have a Z-average molecular weight (Mz) of 1,000 or more and 15,000 or less, preferably 9,500 or less, and more preferably 4,000 or less. If the Z-average molecular weight of the tackifier resin is within the above-mentioned range, the tackifier resin will be well mixed with the acrylic adhesive, and the adhesiveness of the resulting cured product will be improved.

[0045] The tackifier resin must have a ratio of Z-average molecular weight to weight-average molecular weight (Mz / Mw) of 1.0 or more and 2.5 or less, preferably 2.0 or less, and more preferably 1.5 or less. If the Mz / Mw of the tackifier resin is within the above-mentioned range, the tackifier resin will be well mixed with the acrylic adhesive, and the adhesiveness of the resulting cured product will be improved.

[0046] Here, the tackifier resin needs to have a softening point of 70°C or more and 170°C or less, preferably 80°C or more, more preferably 90°C or more, preferably 160°C or less, and more preferably 150°C or less. If the softening point is 70°C or more, the heat resistance of the obtained cured product can be ensured. On the other hand, if the softening point is 170°C or less, the tackifier resin is well mixed with the acrylic adhesive, and the adhesiveness of the obtained cured product is improved. Furthermore, when the curable adhesive composition is applied, the curable adhesive composition can be well spread on the surface to be applied.

[0047] In addition, the tackifier resin preferably has an acid value of 0.01 KOHmg / g or more, more preferably 0.1 KOHmg / g or more, even more preferably 0.5 KOHmg / g or more, and preferably 300 KOHmg / g or less. If the oxidation of the tackifier resin is within the above-mentioned range, the adhesiveness of the cured product (especially the adhesiveness to inorganic materials) can be further improved.

[0048] [Content] The content of the tackifier resin in the curable adhesive composition is not particularly limited, but is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, particularly preferably 5 parts by mass or more, and preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less, per 100 parts by mass of the acrylic adhesive. If the content of the tackifier resin is within the above-mentioned range, the adhesiveness of the cured product can be further improved.

[0049] <Conductive particles> The curable adhesive composition may optionally contain conductive particles. By using a curable adhesive composition containing conductive particles (also called a "conductive resin composition"), a cured product having electrical conductivity can be formed. The cured product made of the conductive resin composition can be used favorably as a cell connection part of a photoelectric conversion element.

[0050] Here, the conductive particles are not particularly limited as long as they are particles made of a conductive material. Specific examples of conductive particles include particles made of metals such as Ag, Au, Cu, Al, In, Sn, Bi, Pb, and alloys containing these metals, and oxides thereof, conductive carbon particles, and particles in which the surface of organic compound particles or inorganic compound particles such as resin particles is coated with a conductive material such as metals such as Ag, Au, Cu, and oxides of these metals, for example, Au / Ni alloy. These may be used alone or in combination of two or more.

[0051] The conductive particles preferably have an average particle size of 0.5 μm or more and 30 μm or less. Furthermore, the content of the conductive particles in the curable adhesive composition is preferably 0.1 volume % or more and 90 volume % or less.

[0052] <Method of preparing curable adhesive composition> The method for preparing the curable adhesive composition is not particularly limited. The curable adhesive composition can be prepared, for example, by mixing the above-mentioned components by a known method.

[0053] (Photoelectric conversion element and photoelectric conversion element module) The photoelectric conversion element of the present invention comprises, at any site, a cured product made of the above-mentioned curable adhesive composition.

[0054] An example of the photoelectric conversion element of the present invention is a photoelectric conversion cell including a first substrate having a photoelectrode, a second substrate having a counter electrode facing the photoelectrode, two partition walls interposed between the first substrate and the second substrate and facing each other, and an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls. The photoelectric conversion element can include a cured product of the above-mentioned curable adhesive composition (which usually does not contain conductive particles) as at least one of the two partition walls.

[0055] Another example of the photoelectric conversion element of the present invention is a photoelectric conversion cell including a first substrate having a photoelectrode, a second substrate having a counter electrode facing the photoelectrode, two partition walls facing each other and interposed between the first substrate and the second substrate, and an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls, and further including at least one of a cell connection part capable of electrically connecting the photoelectrode to a counter electrode belonging to another photoelectric conversion cell and a cell connection part capable of electrically connecting the counter electrode to a photoelectrode belonging to another photoelectric conversion cell. The photoelectric conversion element may include a cured product made of a curable adhesive composition containing the conductive particles described above as at least one of the cell connection parts. The photoelectric conversion element may also include a cured product of a curable adhesive composition (which does not usually contain conductive particles) as at least one of the two partition walls.

[0056] The various members in the photoelectric conversion element of the present invention described above can be the same as those exemplified in the description of the "solar cell module 100" described later.

[0057] The photoelectric conversion element module of the present invention can be produced by connecting a plurality of the above-mentioned photoelectric conversion elements of the present invention in series and / or in parallel. The photoelectric conversion element module of the present invention includes, for example, a cured product of the above-mentioned curable adhesive composition as a partition wall that separates a plurality of photoelectric conversion cells (photoelectric conversion elements, hereinafter also simply referred to as "cells") constituting the module, or as a cell connection part that electrically connects the conductive layer of the photoelectrode and the conductive layer of the counter electrode.

[0058] Furthermore, since the photoelectric conversion element module of the present invention has the above-mentioned partition walls, cell connection parts, etc. formed from a cured material with excellent adhesive properties, it is possible to exhibit excellent photoelectric conversion characteristics by, for example, sufficiently suppressing leakage of the electrolyte. In particular, according to the studies of the present inventors, when conventional curable adhesive compositions are used to produce photoelectric conversion element modules, there are cases where the cured product cannot exhibit sufficient adhesiveness depending on the material of the adherend, such as a resin film or a conductive layer, or the amount of residual dye (amount of residual sensitizing dye) on the surface of the adherend. However, the cured product formed from the above-mentioned curable adhesive composition can exhibit good adhesiveness without being significantly affected by the properties of the adherend.

[0059] Here, the photoelectric conversion element module of the present invention may be a solar cell module formed by connecting a plurality of photoelectric conversion cells in series, for example, a solar cell module having a Z-type integrated structure. Note that, examples of the integrated structure of the solar cell module include, in addition to the Z-type module, a series connection structure such as a W-type module or a monolithic module, or a parallel connection structure, but are not limited thereto.

[0060] As an example of the photoelectric conversion element module of the present invention, a dye-sensitized solar cell module having a Z-shaped integration structure is, without being particularly limited thereto, a solar cell module 100 as shown in a cross-sectional view in the thickness direction in FIG. 1.

[0061] The solar cell module 100 is a solar cell module in which a plurality of cells (four in the illustrated example) partitioned by partition walls 8 are connected in series, and has a so-called Z-shaped integrated structure. Here, the solar cell module 100 has a structure in which a first substrate 3 including a first base material 1 and a plurality of photoelectrodes 2 (four in the illustrated example) spaced apart from each other on the first base material 1, and a second substrate 7 including a second base material 5 and a plurality of counter electrodes 6 (four in the illustrated example) spaced apart from each other on the second base material 5 are bonded together with a partition wall 8 interposed between the first substrate 3 and the second substrate 7 such that the photoelectrodes 2 and counter electrodes 6 forming each cell face each other via an electrolyte layer 4 (i.e., to form a cell), and between adjacent cells, the photoelectrode 2 of one cell and the counter electrode 6 of the other cell are electrically connected via a cell connection part 9. Each cell of the solar cell module 100 includes a photoelectrode 2, a counter electrode 6 facing the photoelectrode 2, and an electrolyte layer 4 provided between the photoelectrode 2 and the counter electrode 6.

[0062] The solar cell module 100 includes a first extraction electrode 11A connected to the photoelectrode conductive layer 21 constituting the photoelectrode 2 via a first electrical connection portion 12A, and a second extraction electrode 11B connected to the counter electrode conductive layer 61 constituting the counter electrode 6 via a second electrical connection portion 12B.

[0063] <First board> Here, the first substrate 3 of the solar cell module 100 shown in FIG. 1 includes a first base material 1 and a plurality of photoelectrodes 2 provided on the first base material 1 at a distance from each other. The photoelectrode 2 includes a photoelectrode conductive layer 21 provided on the first base material 1 and a porous semiconductor fine particle layer 22 provided on a part of the photoelectrode conductive layer 21. The photoelectrode conductive layer 21 is provided with a gap therebetween. The photoelectrodes 2 adjacent to each other are provided so as to be electrically insulated from each other. This insulation is not particularly limited, and can be achieved, for example, by a partition wall 8 present in the gap between the photoelectrode conductive layers 21 adjacent to each other.

[0064] The first substrate 1 is not particularly limited and may be appropriately selected from known light-transmitting substrates. For example, the first substrate 1 may be a known transparent substrate having transparency in the visible region, such as transparent resin or glass. Among them, it is preferable to use a transparent resin formed into a film, that is, a resin film, as the first substrate 1. Although the resin film substrate has inferior barrier properties of the substrate itself compared to substrates such as glass, the barrier properties can be greatly improved by adopting the structure of the present invention. In addition, by adopting a resin film as the first substrate 1, it is possible to impart lightness and flexibility to the solar cell module, and thus it can be applied to various uses.

[0065] Examples of transparent resins that can be used to form a resin film include synthetic resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), syndiotactic polystyrene (SPS), polyphenylene sulfide (PPS), polycarbonate (PC), polyarylate (PAr), polysulfone (PSF), polyestersulfone (PES), polyetherimide (PEI), transparent polyimide (PI), and cycloolefin polymer (COP).

[0066] Furthermore, the photoelectrode conductive layer 21 is not particularly limited, and may be a conductive layer made of a metal mesh made of Au, Ag, Cu, or the like, a conductive layer formed by applying metal nanoparticles such as Ag nanoparticles or fine Ag wires, a conductive layer made of a composite metal oxide such as indium-tin oxide (ITO), indium-zinc oxide (IZO), or fluorine-doped tin (FTO), a carbon-based conductive layer containing carbon nanotubes or graphene, or a conductive layer made of a conductive polymer such as PEDOT / PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate). These materials can be appropriately selected depending on the compatibility with other materials. In addition, a plurality of these conductive layers may be laminated on the first substrate 1, or the various conductive materials as described above that can be used to form these conductive layers may be mixed to form one conductive layer. The photoelectrode conductive layer 21 can be formed on the first substrate 1 by a known method such as a combination of sputtering and etching, or screen printing.

[0067] Optionally, an undercoat layer (not shown) can be provided on the conductive layer 21 for the photoelectrode. Here, when the electrolyte layer 4 described later is made of a liquid, the electrolyte reaches the conductive layer 21 for the photoelectrode through the porous semiconductor fine particle layer 22, and an internal short circuit phenomenon called reverse electron transfer, in which electrons leak from the conductive layer 21 for the photoelectrode to the electrolyte layer 4, may occur. Therefore, there is a risk that a reverse current unrelated to the irradiation of light will occur, resulting in a decrease in the photoelectric conversion efficiency. Thus, such an internal short circuit phenomenon can be prevented by providing an undercoat layer on the conductive layer 21 for the photoelectrode. Furthermore, by providing an undercoat layer on the conductive layer 21 for the photoelectrode, the adhesion between the porous semiconductor fine particle layer 22 and the conductive layer 21 for the photoelectrode can be improved. The undercoat layer is not particularly limited as long as it is a material that can prevent an internal short circuit phenomenon (is unlikely to cause an interface reaction). For example, it may be a layer containing a material such as titanium oxide, niobium oxide, or tungsten oxide. In addition, the method of forming the undercoat layer may be a method of directly sputtering the above-mentioned material onto the conductive layer 21 for photoelectrode, or a method of applying a solution in which the above-mentioned material is dissolved in a solvent, a solution in which a metal hydroxide that is a precursor of a metal oxide is dissolved, or a solution containing a metal hydroxide obtained by dissolving an organometallic compound in a mixed solvent containing water onto the conductive layer 21 for photoelectrode, drying, and sintering as necessary.

[0068] Furthermore, the porous semiconductor fine particle layer 22 carrying (adsorbing) a sensitizing dye is not particularly limited, and a porous semiconductor fine particle layer formed by adsorbing a sensitizing dye such as an organic dye or a metal complex dye to a porous semiconductor fine particle layer containing particles of an oxide semiconductor such as titanium oxide, zinc oxide, or tin oxide can be used. Examples of the organic dye include cyanine dyes, merocyanine dyes, oxonol dyes, xanthene dyes, squarylium dyes, polymethine dyes, coumarin dyes, riboflavin dyes, and perylene dyes. Examples of the metal complex dye include phthalocyanine complexes and porphyrin complexes of metals such as iron, copper, and ruthenium. For example, N3, N719, N749, D102, D131, D150, N205, HRS-1, and HRS-2 are representative examples of sensitizing dyes. It is preferable that the organic solvent in which the sensitizing dye is dissolved is degassed and purified by distillation in advance to remove moisture and gas present in the solvent. Preferred organic solvents include alcohols such as methanol, ethanol, and propanol, nitriles such as acetonitrile, halogenated hydrocarbons, ethers, amides, esters, carbonates, ketones, hydrocarbons, aromatics, and nitromethane.

[0069] The porous semiconductor fine particle layer 22 can be formed on the photoelectrode conductive layer 21 by a known method such as screen printing or coating. The sensitizing dye can be adsorbed on the porous semiconductor fine particle layer by a known method such as immersing the porous semiconductor fine particle layer in a solution containing the sensitizing dye.

[0070] <Second board> The second substrate 7 of the solar cell module 100 includes a second base material 5 and a plurality of counter electrodes 6 spaced apart from one another on the second base material 5. The counter electrode 6 includes a counter electrode conductive layer 61 provided on the second base material 5, and a catalyst layer 62 provided on a portion of the counter electrode conductive layer 61. The catalyst layer 62 faces the porous semiconductor fine particle layer 22 of the photoelectrode 2. Adjacent counter electrodes 6 are provided so as to be electrically insulated from each other. This insulation is not particularly limited, and can be achieved, for example, by providing a partition wall 8 in the gap between the adjacent counter electrodes 6.

[0071] The second substrate 5 may be a substrate similar to the first substrate 1, or a substrate that is not transparent, such as a foil or plate of titanium, SUS, aluminum, or the like, and is not susceptible to corrosion by other solar cell components. Among these, for the same reasons as the first substrate 1, it is preferable to form the second substrate 5 using a resin film.

[0072] As the conductive layer 61 for the counter electrode, a conductive layer similar to the conductive layer 21 for the photoelectrode can be used.

[0073] Furthermore, the catalyst layer 62 is not particularly limited, and any catalyst layer containing components that can function as a catalyst, such as conductive polymers, carbon nanostructures, precious metal particles, and mixtures of carbon nanostructures and precious metal particles, can be used. Examples of the conductive polymer include polythiophenes such as poly(thiophene-2,5-diyl), poly(3-butylthiophene-2,5-diyl), poly(3-hexylthiophene-2,5-diyl), and poly(2,3-dihydrothieno-[3,4-b]-1,4-dioxin) (PEDOT); polyacetylene and its derivatives; polyaniline and its derivatives; polypyrrole and its derivatives; and poly(p-xylylenetetrahydrofuran). tetrahydrothiophenium chloride), polyphenylene vinylenes such as poly[(2-methoxy-5-(2'-ethylhexyloxy))-1,4-phenylene vinylene], poly[(2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene)], and poly[2-2',5'-bis(2''-ethylhexyloxy)phenyl]-1,4-phenylene vinylene]. Examples of carbon nanostructures include natural graphite, activated carbon, artificial graphite, graphene, carbon nanotubes, and carbon nanobuds. The noble metal particles are not particularly limited as long as they have a catalytic effect, and known noble metal particles such as platinum metal, palladium metal, and ruthenium metal can be appropriately selected and used.

[0074] The method for forming the catalyst layer is not particularly limited, and a known method can be appropriately selected and used. For example, a mixed liquid obtained by dissolving or dispersing a conductive polymer, a carbon nanostructure, precious metal particles, or both a carbon nanostructure and precious metal particles in a suitable solvent is applied or sprayed onto the conductive film, and the solvent of the mixed liquid is dried. When using carbon nanostructures or precious metal particles, the mixed liquid may further contain a binder. As the binder, it is preferable to use a polymer having a functional group such as a hydroxyl group, a carboxyl group, a sulfonyl group, a phosphoric acid group, or a sodium salt of these functional groups, in terms of the dispersibility of the carbon nanostructure and the adhesion to the substrate.

[0075] <Bulkhead> Furthermore, the partition wall 8 of the solar cell module 100 is provided between the first substrate 3 and the second substrate 7, and surrounds each of the electrolyte layer 4 and the cell connection portion 9. In other words, the space in which the electrolyte layer 4 is provided and the space in which the cell connection portion 9 is provided are defined by the first substrate 3, the second substrate 7, and the partition wall 8.

[0076] 1, the partition walls 8 are provided on one widthwise side of each cell (left side in FIG. 1) between the photoelectrode conductive layer 21 of the photoelectrode 2 of the first substrate 3 and the second base material 5 of the second substrate 7, and on the other widthwise side of each cell (right side in FIG. 1) between the photoelectrode conductive layer 21 of the photoelectrode 2 of the first substrate 3 and the counter electrode conductive layer 61 (a portion located on the other widthwise side of the portion where the catalyst layer 62 is formed) of the counter electrode 6 of the second substrate 7. Then, between the partition walls 8, the electrolyte layers 4 and the cell connection portions 9 are provided alternately.

[0077] The partition wall 8 preferably has excellent adhesion between substrates, resistance to electrolytes (chemical resistance), and durability at high temperature and humidity (humid heat resistance). In the photoelectric conversion element module of the present invention, a cured product of the above-mentioned curable adhesive composition can be preferably used as such partition wall 8. In addition, apart from the above-mentioned predetermined curable adhesive composition, the partition material capable of forming the partition wall 8 is not particularly limited as long as it is capable of bonding the first substrate 3 and the second substrate 7 and sealing the electrolyte layer 4, and examples of the partition material include non-conductive thermoplastic resins, thermosetting resins, and actinic radiation (light, electron beam) curable resins. More specifically, examples of the partition material include fluorine-based resins, silicone-based resins, olefin-based resins, and polyamide-based resins.

[0078] The above-mentioned partition wall 8 is not particularly limited, and can be formed, for example, by applying an uncured curable adhesive composition to the position where the partition wall 8 is to be formed, and curing the applied uncured curable adhesive composition.

[0079] <Electrolyte layer> The electrolyte layer 4 of the solar cell module 100 is provided in a space surrounded by the porous semiconductor fine particle layer 22 of the photoelectrode 2, the catalyst layer 62 of the counter electrode 6, and the partition wall 8. The electrolyte layer 4 is not particularly limited, and can be formed using any electrolyte solution, gel electrolyte, or solid electrolyte that can be used in dye-sensitized solar cells.

[0080] <Cell connection part> Furthermore, the cell connection part 9 of the solar cell module 100 electrically connects adjacent cells in series. Specifically, the cell connection part 9 electrically connects the photoelectrode conductive layer 21 of the photoelectrode 2 of the cell located on the right side in Fig. 1 to the counter electrode conductive layer 61 of the counter electrode 6 of the cell located on the left side in Fig. 1.

[0081] The cell connection part 9 of the solar cell module 100 is composed of wiring 91 formed on the photoelectrode conductive layer 21 of the photoelectrode 2 at a distance from the porous semiconductor fine particle layer 22, and a conductive resin part 92 filled in a space surrounded by the first substrate 3, the second substrate 7, and the partition wall 8. In the solar cell module 100 shown in FIG. 1, the cell connection part 9 is formed using the wiring 91 and the conductive resin part 92, but in the photoelectric conversion element module of the present invention, the cell connection part may be formed using only the conductive resin part. Also, the wiring may be formed on the counter electrode conductive layer 61 of the counter electrode 6.

[0082] Here, the wiring 91 is not particularly limited, and wiring made of a conductive material such as a metal or metal oxide can be used. Among them, from the viewpoint of reducing the resistance of the cell connection portion 9 and increasing the photoelectric conversion efficiency of the photoelectric conversion element module, it is preferable to use metal wiring such as copper wiring, gold wiring, silver wiring, and aluminum wiring as the wiring 91. Note that, as a method for forming the wiring 91 on the photoelectrode conductive layer 21, a known formation method such as sputtering or screen printing can be used.

[0083] In addition, in the photoelectric conversion element module of the present invention, a cured product of a curable adhesive composition (conductive resin composition) containing the above-mentioned acrylic adhesive, a specified tackifier resin, and conductive particles can be preferably used as the conductive resin part 92. In addition to the above-mentioned predetermined curable adhesive composition, the composition capable of forming the conductive resin portion is not particularly limited as long as it contains a resin and conductive particles. Examples of the resin in such a conductive resin composition include epoxy resins such as bisphenol type epoxy resin, novolac type epoxy resin, cyclic epoxy resin, and alicyclic epoxy resin; silicone resin; and the like. Any curing agent such as a radical initiator, a cationic curing agent, or an anionic curing agent can be used for the resin, and the polymerization type is not particularly limited, such as addition polymerization or ring-opening polymerization.

[0084] The cell connection part 9 using the above-mentioned conductive resin part 92 is not particularly limited, and can be formed, for example, by filling an uncured conductive resin composition in the position where the cell connection part 9 is to be formed, and curing the filled uncured conductive resin composition.

[0085] <Extraction electrode> The first and second extension electrodes 11A and 11B, which are connected to the photoelectrode 2 and the counter electrode 6, respectively, have conductors made of a general conductive material, without any particular limitation. Examples of such conductors include conductors made of a metal material selected from the group consisting of copper, aluminum, nickel, iron, etc., and alloy materials containing these metal materials. Among these, electrodes using copper as a conductor or electrodes using stainless steel as a base material are preferred. The thickness of the conductor is preferably 0.001 mm or more and 0.5 mm or less. As the extraction electrode, it is possible to use, as desired, the above-mentioned conductor partially coated with a conductive material that can be used as a material for forming the first and second electrical connection portions 12A and 12B.

[0086] Furthermore, the first electrical connection portion 12A connecting the photoelectrode conductive layer 21 constituting the photoelectrode 2 and the first extension electrode 11A, and the second electrical connection portion 12B connecting the counter electrode conductive layer 61 constituting the counter electrode 6 and the second extension electrode 11B are not particularly limited and can be formed from a general electrical connection material. Preferably, from the viewpoint of increasing the photoelectric conversion efficiency by reducing resistance, the first and second electrical connection portions 12A and 12B can be formed from the above-mentioned acrylic adhesive, a cured product of a curable adhesive composition (conductive resin composition) containing a predetermined tackifier resin and conductive particles, a conductive tape product in which a conductor and a conductive adhesive are integrated, or solder. The solder may contain tin, silver, copper, bismuth, lead, flux components, etc. It is preferable that the solder can be formed at a temperature that does not affect the elements or the base material.

[0087] Although not shown in FIG. 1, the first electrical connection portion 12A and the second electrical connection portion 12B may be connected to the photoelectrode 2 or the counter electrode 6 via current collector lines formed in the same manner as the wiring 91, respectively.

[0088] <Other configurations> The photoelectric conversion element module of the present invention may include configurations other than those described above. The other configurations are not particularly limited, and examples thereof include a gas barrier film including one or more photoelectric conversion cells.

[0089] <Method for manufacturing a photoelectric conversion element and a photoelectric conversion element module> The photoelectric conversion element and the photoelectric conversion element module of the present invention are not particularly limited as long as the above-described curable adhesive composition can be cured, and can be manufactured by known methods such as a vacuum bonding method (ODF method) and an end seal method. As such known methods, for example, the methods described in International Publication No. 2018 / 025821, International Publication No. 2017 / 169986, International Publication No. 2007 / 046499, and JP-A-2006-004827 can be adopted.

Examples

[0090] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, the following methods were used for various measurements and evaluations.

[0091] <Mn, Mw, Mz, and Mz / Mw> The tackifying resin was analyzed by gel permeation chromatography to determine the number average molecular weight (Mn), weight average molecular weight (Mw), and Z average molecular weight (Mz) in terms of standard polystyrene conversion values, and the ratio of the Z average molecular weight to the weight average molecular weight (Mz / Mw) was calculated. For the gel permeation chromatography analysis, "HLC-8320GPC" manufactured by Tosoh Corporation was used as the measuring device, and a column obtained by connecting three "TSKgel SuperMultipore HZ" columns manufactured by Tosoh Corporation was used. Using tetrahydrofuran as the solvent, the measurement was performed at 40 °C with a flow rate of 1.0 mL / min. <Softening point> The softening point of the tackifying resin was measured in accordance with JIS K 2207. <Acid value> The acid value of the tackifying resin was measured in accordance with JIS K 0070. <Coating thickness> The coating thicknesses of Composition A and Composition B were measured as follows. When manufacturing the dye-sensitized solar cell module, the total thickness of the first substrate and the second substrate was subtracted from the overall thickness when the first substrate and the second substrate were bonded via Composition A and B, and this was defined as the coating thickness (μm). For the thickness measurement, a thickness gauge (manufactured by Teclock Corporation, product name "Constant pressure thickness gauge compliant with JIS K6250") was used. <Amount of residual dye> The amount of residual dye was measured as follows using X-ray photoelectron spectroscopy (XPS) as the ratio of residual Ru element on the substrate. A sample film was cut out from the obtained transparent conductive substrate (such as a PEN film coated with ITO) of the first substrate. The intensity of the Ru3d narrow spectrum obtained by analyzing the surface of the obtained sample film by X-ray photoelectron spectroscopy (XPS) method was measured to determine the amount of residual dye (%) on the substrate. <T-peel adhesive strength> The T-peel adhesive strength between the first substrate and the second substrate bonded via Composition A and Composition B was measured as follows in accordance with JIS K6854. In the same manner as in each Example, a substrate after light irradiation was produced by bonding the first substrate and the second substrate together. The adhesive strength (N / 10 mm) of the bonded substrate was measured by a Tensilon (registered trademark) tester when the substrate was clamped on both sides and pulled at a speed of 300 mm / min. <Peeling mode> After the above T-peel adhesion measurement, both the first substrate and the second substrate (both films) were visually observed and evaluated as follows. Cohesive failure: some cured material remains in both films. Interfacial peeling: The cured material remains only on one film, and no cured material remains on the other film. In the case of interfacial peeling, there is a risk of moisture penetrating from the interface, which may impair the reliability of the photoelectric conversion element module. Therefore, it can be said that the most preferable ones are those with high T-peel adhesion strength and a peel mode of cohesive failure, and the least preferable ones are those with low T-peel adhesion strength and a peel mode of interfacial peeling. In Tables 1 and 2 below, cohesive failure is indicated as "cohesive" and interfacial peeling is indicated as "interface." <Peeling of cell connection and first substrate> The fabricated dye-sensitized solar cell module was visually observed to check for peeling between the cell connection and the first substrate. Specifically, the areas where the cell connection and the first substrate had peeled off were confirmed as air bubbles (or lines of continuous air bubbles), and the presence or absence of such bubbles was checked. Note that a rating of "a small amount" means that the dye-sensitized solar cell module still functions well, and is not a fatal defect. <Whether or not electrolyte is leaking> The produced dye-sensitized solar cell module was visually observed to check for electrolyte leakage.

[0092] (Preparation of tackifier resin) The following resins were prepared as tackifier resins. <Rosin Ester A> Arakawa Chemical Co., Ltd., product name "Ester Gum AA-G", softening point: 82°C, acid value: 7KOHmg / g, Mn: 732, Mw: 898, Mz: 1087 Mz / Mw: 1.21 <Acid-modified C5 / C9 resin B> Manufactured by Zeon Corporation, product name "Quintone (registered trademark) D295", softening point: 94 °C, acid value: 8 KOHmg / g, Mn: 1300, Mw: 2720, Mz: 6420, Mz / Mw: 2.36 <C5 / C9 resin C> Manufactured by Zeon Corporation, product name "Quintone DX390N", softening point: 93 °C, acid value: 0 KOHmg / g, Mn: 1260, Mw: 2490, Mz: 5910, Mz / Mw: 2.37 <Dicyclopentadiene (DCPD)-based resin D> Manufactured by Zeon Corporation, product name "Quintone 1500", softening point: 100 °C, acid value: 0 KOHmg / g, Mn: 380, Mw: 670, Mz: 1300 Mz / Mw: 1.94 <C5 / C9 resin E> Manufactured by Zeon Corporation, product name "Quintone G115", softening point: 99 °C, acid value: 0 KOHmg / g, Mn: 1500, Mw: 4190, Mz: 13190, Mz / Mw: 3.15) <Acid-modified C5 / C9 resin F> Manufactured by Zeon Corporation, product name "Quintone E200SN", softening point: 102 °C, acid value: 1.5 KOHmg / g, Mn: 1495, Mw: 5106, Mz: 16567, Mz / Mw: 3.24) <Acid-modified C5 / C9 resin G> Manufactured by Zeon Corporation, product name "Quintone E200SN" Softening point: 102 °C Acid value: 1.5 KOHmg / g Mn: 1420 Mw: 4314 Mz: 13015 Mz / Mw: 3.04 Note that the acid-modified C5 / C9 resin G is a different product number from the acid-modified C5 / C9 resin F.

[0093] (Example 1) <Preparation of electrolyte> The following substances were added to γ-butyrolactone to the following concentrations, stirred for 1 hour by vibration using an ultrasonic cleaner, and then left standing in the dark for 24 hours or more to prepare an electrolyte. Iodine: 0.04 mol / L Lithium iodide: 0.10 mol / L Tetrabutylammonium iodide: 0.40 mol / L <Preparation of dye solution> 72 mg of ruthenium complex dye (N719) was placed in a 200 mL measuring flask. 190 mL of dehydrated ethanol was added and stirred. The measuring flask was then stoppered and stirred for 60 minutes using vibrations from an ultrasonic cleaner. The solution was kept at room temperature, and then dehydrated ethanol was added to bring the total volume to 200 mL to prepare a dye solution. <Preparation of Composition A> 100 parts by mass of an acrylic adhesive (manufactured by ThreeBond, product name "TB3035B") and 1 part by mass of rosin ester A were mixed using an automatic revolution mixer to prepare a curable adhesive composition (composition A) that did not contain conductive particles. <Preparation of Composition B> A curable adhesive composition containing conductive particles (conductive resin composition, composition B) was prepared by mixing 100 parts by mass of an acrylic adhesive (manufactured by ThreeBond, product name "TB3035B"), 1 part by mass of rosin ester A, and conductive particles (manufactured by Sekisui Plastics, product name "Micropearl AU", average particle diameter (median diameter): 8 μm). The amount of conductive particles was adjusted to 5% by volume. <Preparation of the first substrate> A transparent conductive layer (amorphous indium-tin oxide (ITO)) serving as a conductive layer for a photoelectrode was coated on a transparent substrate (polyethylene naphthalate (PEN) film, thickness: 200 μm) as the first substrate to obtain a transparent conductive substrate (sheet resistance: 13 ohm / sq.). A conductive silver paste (K3105, manufactured by Pelnox Co., Ltd.) was printed and applied as wiring (current collector) on the surface of the transparent conductive layer side of this transparent conductive substrate by screen printing at intervals corresponding to the photoelectrode cell width, and the wiring was produced by heating and drying for 15 minutes in a hot air circulation type oven at 150 degrees. The transparent conductive substrate having the obtained wiring was set on a coating coater with the wiring-formed surface facing up, and a 1.6% diluted solution of Orgatic PC-600 (manufactured by Matsumoto Fine Chemical Co., Ltd.) was applied with a wire bar at a sweep speed (10 mm / sec). The obtained coating film was dried at room temperature for 10 minutes, and then heated and dried for another 10 minutes at 150 degrees Celsius to produce an undercoat layer on the transparent conductive substrate. The surface of the transparent conductive substrate on which the undercoat layer was formed was subjected to laser treatment at intervals corresponding to the width of the photoelectrode cell to form insulating lines. A high-pressure mercury lamp (rated lamp power: 400 W) was placed 10 cm away from the mask-attached surface, and after irradiating electromagnetic waves for 1 minute, titanium oxide paste (PECC-C01-06, Pexel Technologies, Inc.) was immediately applied using a Baker-type applicator. After drying the paste at room temperature for 10 minutes, the protective film (NBO-0424, Fujimori Kogyo Co., Ltd.) on the upper side of the mask film was peeled off and removed, and the film was heated and dried for another 5 minutes in a 150°C hot air circulating oven to form a porous semiconductor fine particle layer (length: 60 mm, width: 5 mm). Thereafter, the transparent conductive substrate on which the porous semiconductor particle layer (length: 60 mm, width: 5 mm) was formed was immersed in the prepared dye solution (40°C) and the dye was adsorbed while being gently stirred. After 90 minutes (adsorption time), the dye-adsorbed titanium oxide film was removed from the dye adsorption container, washed with ethanol and dried, and the remaining mask film was peeled off to prepare a first substrate equipped with a photoelectrode. <Preparation of the second substrate> A transparent conductive layer (amorphous ITO) was coated on the second substrate (a transparent substrate, thickness: 200 μm) to form a conductive layer for the counter electrode, thereby obtaining a transparent conductive substrate (sheet resistance: 13 ohm / sq.). The surface of the transparent conductive layer side of this transparent conductive substrate was subjected to laser processing at intervals corresponding to the width of the platinum film pattern to form insulating lines. Next, a metal mask with openings (length: 60 mm, width: 5 mm) punched out was placed over it, and a platinum film pattern (catalyst layer) was formed by sputtering, to obtain a second substrate in which the catalyst layer-forming portion had a light transmittance of about 72%. At this time, when the first substrate and the second substrate were placed over each other with their conductive surfaces facing each other, the porous semiconductor fine particle layer and the catalyst layer were structured to coincide with each other. <Fabrication of dye-sensitized solar cell module> The catalyst layer-formed surface of the second substrate was fixed on an aluminum suction plate using a vacuum pump. Next, composition B (conductive resin composition) was applied in a line shape to the position between the catalyst layers that overlaps with the wiring between the photoelectrode cells when the second substrate was placed opposite the first substrate, and composition A, which is a partition material, was applied to the outer periphery of the catalyst layers sandwiching the line by a dispenser device. Then, a predetermined amount of electrolyte was applied to the catalyst layer portion, and the rectangular catalyst layer and the porous semiconductor fine particle layer of the same shape were laminated in a reduced pressure environment using an automatic lamination device so that they were structured to face each other, and light was irradiated from a metal halide lamp from the first substrate side, and then light was irradiated from the second substrate side. Then, a connector including a plurality of cells was cut out from the substrates after lamination, and a conductive copper foil tape (CU7636D, manufactured by Sony Chemical & Information Device Corporation, thickness of the copper foil as a conductor: 35 μm) that forms an extraction electrode was attached to the wiring arranged at both ends (extraction electrode portion) of the connector, to prepare a dye-sensitized solar cell module.

[0094] Example 2 When preparing compositions A and B, the amount of rosin ester A was changed from 1 part by mass to 5 parts by mass. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0095] Example 3 The first substrate was prepared as follows. Otherwise, the electrolyte solution, the dye solution, the composition A, the composition B, the second substrate, and the dye-sensitized solar cell module were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1. <Preparation of the first substrate> A transparent conductive layer (amorphous indium-tin oxide (ITO)) serving as a conductive layer for a photoelectrode was coated on a transparent substrate (polyethylene naphthalate (PEN) film, thickness: 200 μm) as the first substrate to obtain a transparent conductive substrate (sheet resistance: 13 ohm / sq.). A conductive silver paste (K3105, manufactured by Pelnox Co., Ltd.) was printed and applied as wiring (current collector) on the surface of the transparent conductive layer side of this transparent conductive substrate by screen printing at intervals corresponding to the photoelectrode cell width, and the wiring was produced by heating and drying for 15 minutes in a hot air circulation type oven at 150 degrees. The transparent conductive substrate having the obtained wiring was set on a coating coater with the wiring-formed surface facing up, and a 1.6% diluted solution of Orgatic PC-600 (manufactured by Matsumoto Fine Chemical Co., Ltd.) was applied with a wire bar at a sweep speed (10 mm / sec). The obtained coating film was dried at room temperature for 10 minutes, and then heated and dried for another 10 minutes at 150 degrees Celsius to produce an undercoat layer on the transparent conductive substrate. The surface of the transparent conductive substrate on which the undercoat layer was formed was subjected to laser treatment at intervals corresponding to the width of the photoelectrode cell to form insulating lines. A high-pressure mercury lamp (rated lamp power: 400 W) light source was placed 10 cm away from the substrate, and after irradiating the substrate with electromagnetic waves for 1 minute, titanium oxide paste (PECC-C01-06, Pexel Technologies, Inc.) was immediately applied using a Baker-type applicator. The paste was dried at room temperature for 10 minutes, and then heated and dried for an additional 5 minutes in a hot air circulating oven at 150°C to form a porous semiconductor particle layer (length: 60 mm, width: 5 mm). Then, the transparent conductive substrate on which the porous semiconductor particle layer (length: 60 mm, width: 5 mm) was formed was immersed in the prepared dye solution (40°C) and the dye was adsorbed while being gently stirred. After 90 minutes (adsorption time), the dye-adsorbed titanium oxide film was taken out of the dye adsorption container, washed with ethanol and dried to prepare a first substrate equipped with a photoelectrode.

[0096] Example 4 When preparing compositions A and B, the amount of rosin ester A was changed from 1 part by mass to 10 parts by mass. Except for this, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 3, and various evaluations were performed. The results are shown in Table 1.

[0097] Example 5 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (polyethylene terephthalate (PET) film, thickness: 200 μm) with a transparent conductive layer (crystalline indium tin oxide (ITO)) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.

[0098] Example 6 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (PET film, thickness: 200 μm) with a transparent conductive layer (crystalline ITO) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 2, and various evaluations were performed. The results are shown in Table 1.

[0099] Example 7 The first substrate was prepared as follows. Otherwise, the electrolyte solution, the dye solution, the composition A, the composition B, the second substrate, and the dye-sensitized solar cell module were prepared in the same manner as in Example 6, and various evaluations were performed. The results are shown in Table 1. <Preparation of the first substrate> A transparent conductive layer (crystalline ITO) serving as a conductive layer for a photoelectrode was coated on a transparent substrate (PET film, thickness: 200 μm) serving as a first substrate to obtain a transparent conductive substrate (sheet resistance: 13 ohm / sq.). A first substrate provided with a photoelectrode was produced in the same manner as in Example 3, except that this transparent conductive substrate was used.

[0100] Example 8 When preparing compositions A and B, acid-modified C5 / C9 resin B was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 2, and various evaluations were performed. The results are shown in Table 1.

[0101] Example 9 When preparing compositions A and B, acid-modified C5 / C9 resin B was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 6, and various evaluations were performed. The results are shown in Table 1.

[0102] Example 10 When preparing compositions A and B, C5 / C9 resin C was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 2, and various evaluations were performed. The results are shown in Table 1.

[0103] Example 11 When preparing compositions A and B, DCPD resin D was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 4, and various evaluations were performed. The results are shown in Table 1.

[0104] Example 12 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (PET film, thickness: 200 μm) with a transparent conductive layer (crystalline ITO) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 11, and various evaluations were performed. The results are shown in Table 1.

[0105] Comparative Example 1 An acrylic adhesive (manufactured by ThreeBond, product name "TB3035B") was used as it was for composition A, and no rosin ester A was used when preparing composition B. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 2.

[0106] Comparative Example 2 An acrylic adhesive (manufactured by ThreeBond, product name "TB3035B") was used as it was for composition A, and no rosin ester A was used when preparing composition B. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 3, and various evaluations were performed. The results are shown in Table 2.

[0107] Comparative Example 3 When preparing compositions A and B, 5 parts by mass of C5 / C9 resin E was used instead of 1 part by mass of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 3, and various evaluations were performed. The results are shown in Table 2.

[0108] Comparative Example 4 When preparing compositions A and B, acid-modified C5 / C9 resin F was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 2, and various evaluations were performed. The results are shown in Table 2.

[0109] Comparative Example 5 When preparing compositions A and B, acid-modified C5 / C9 resin G was used instead of rosin ester A. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Example 2, and various evaluations were performed. The results are shown in Table 2.

[0110] Comparative Example 6 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (PET film, thickness: 200 μm) with a transparent conductive layer (crystalline ITO) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Comparative Example 1, and various evaluations were performed. The results are shown in Table 2.

[0111] Comparative Example 7 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (PET film, thickness: 200 μm) with a transparent conductive layer (crystalline ITO) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Comparative Example 4, and various evaluations were performed. The results are shown in Table 2.

[0112] Comparative Example 8 When preparing the first and second substrates, transparent conductive substrates obtained by coating a transparent base material (PET film, thickness: 200 μm) with a transparent conductive layer (crystalline ITO) were used. Otherwise, the electrolyte solution, dye solution, composition A, composition B, first substrate, second substrate, and dye-sensitized solar cell module were prepared in the same manner as in Comparative Example 2, and various evaluations were performed. The results are shown in Table 2.

[0113] [Table 1]

[0114] [Table 2]

[0115] From Tables 1 and 2, the following can be seen: In Examples 1, 2, 8, and 10 and Comparative Examples 1, 4, and 5, the first substrate is prepared using a transparent conductive substrate made of a PEN film and amorphous ITO, and the amount of residual dye in the first substrate is 0%. Comparing these, it is found that Examples 1, 2, 8, and 10, which use a curable adhesive composition containing a specific tackifier resin, have superior adhesiveness of the cured product compared to Comparative Examples 1, 4, and 5. In Examples 3, 4, and 11 and Comparative Examples 2 and 3, the first substrate was prepared using a transparent conductive substrate made of a PEN film and amorphous ITO, and the amount of residual dye in the first substrate was 0.2%. Comparing these, it can be seen that Examples 3, 4, and 11, which used a curable adhesive composition containing a specific tackifier resin, have superior adhesiveness of the cured product compared to Comparative Examples 2 and 3. In Examples 5, 6, and 9 and Comparative Examples 6 and 7, the first substrate was prepared using a transparent conductive substrate made of a PET film and crystalline ITO, and the amount of residual dye in the first substrate was 0%. Comparing these, it can be seen that Examples 5, 6, and 9, which used a curable adhesive composition containing a specific tackifier resin, have superior adhesiveness of the cured product compared to Comparative Examples 6 and 7. In Examples 7 and 12 and Comparative Example 8, the first substrate was prepared using a transparent conductive substrate made of a PET film and crystalline ITO, and the amount of residual dye in the first substrate was 0.2%. Comparing these, it can be seen that Examples 7 and 12, which used a curable adhesive composition containing a specific tackifier resin, have superior adhesiveness of the cured product compared to Comparative Example 8. [Industrial Applicability]

[0116] According to the present invention, it is possible to provide a photoelectric conversion element and a photoelectric conversion element module including a cured product capable of exhibiting excellent adhesive properties. [Explanation of symbols]

[0117] 1 First base material 2. Photoelectrode 3 First board 4 Electrolyte layer 5 Second base material 6 Counter electrode 7 Second board 8 Bulkhead 9 Cell Connection 11A First extraction electrode 11B Second extraction electrode 12A First Electrical Connection 12B Second electrical connection 21 Conductive layer for photoelectrodes 22 Porous semiconductor particle layer 61 Counter electrode conductive layer 62 Catalyst layer 91 Wiring 92 Conductive resin part 100 Solar Modules

Claims

1. A first substrate having a photoelectrode; A second substrate including a counter electrode facing the photoelectrode; Two partition walls that are interposed between the first substrate and the second substrate and face each other; an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls; A photoelectric conversion cell comprising: At least one of the two partition walls is made of a cured product of a curable adhesive composition containing an acrylic adhesive and a tackifier resin, The tackifier resin is at least one of a hydrocarbon resin and a rosin-based resin, the tackifier resin has a number average molecular weight of 200 or more and 2,000 or less, a weight average molecular weight of 500 or more and 5,000 or less, a Z average molecular weight of 1,000 or more and 15,000 or less, and a ratio of the Z average molecular weight to the weight average molecular weight is 1.0 or more and 2.5 or less; The content of the tackifier resin is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the acrylic adhesive, and The tackifier resin has a softening point of 70° C. or higher and 170° C. or lower.

2. A first substrate having a photoelectrode; A second substrate including a counter electrode facing the photoelectrode; Two partition walls that are interposed between the first substrate and the second substrate and face each other; an electrolyte layer provided in a space surrounded by the photoelectrode, the counter electrode, and the two partition walls; Furthermore, at least one of a cell connection part capable of electrically connecting the photoelectrode to a counter electrode belonging to another photoelectric conversion cell and a cell connection part capable of electrically connecting the counter electrode to a photoelectrode belonging to another photoelectric conversion cell, A photoelectric conversion cell comprising: at least one of the cell connection parts of the photoelectric conversion cell contains a cured product of a curable adhesive composition including an acrylic adhesive, a tackifier resin, and conductive particles; The tackifier resin is at least one of a hydrocarbon resin and a rosin-based resin, the tackifier resin has a number average molecular weight of 200 or more and 2,000 or less, a weight average molecular weight of 500 or more and 5,000 or less, a Z average molecular weight of 1,000 or more and 15,000 or less, and a ratio of the Z average molecular weight to the weight average molecular weight is 1.0 or more and 2.5 or less; The content of the tackifier resin is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the acrylic adhesive, and The tackifier resin has a softening point of 70° C. or higher and 170° C. or lower.

3. 3. The photoelectric conversion element according to claim 1, wherein the tackifier resin has a number average molecular weight of 200 or more and 1,000 or less, a weight average molecular weight of 500 or more and 2,000 or less, and a Z average molecular weight of 1,000 or more and 4,000 or less.

4. 4. The photoelectric conversion element according to claim 1, wherein the tackifier resin has an acid value of 0.01 KOHmg / g or more and 300 KOHmg / g or less.

5. 5. A photoelectric conversion element module having a structure in which the photoelectric conversion elements according to claim 1 are connected in series and / or in parallel.

Citation Information

Patent Citations

  • Adhesive resin composition and film using the same

    JP2010090353A

  • Photo-curable composition, use of the same as sealing material, and wet organic solar cell

    JP2010265412A

  • Resin composition, and sealant for dye-sensitized solar cell prepared by using the same

    JP2011144306A

  • Photocurable composition and use of the same as sealing material for wet-type organic solar cell, and wet-type organic solar cell

    JP2013047308A

  • Dye-sensitized solar cell and method for manufacturing the same

    JP2015191986A